CGIAR Centres’ submission on best practices/measures of implementing Article 9 of the ITPGRFA: Views, experiences and best practices as an example of possible options for the national implementation of article 9 of the International Treaty - CGIAR Genebank Platform (2019)
This document presents the updated information on best practices and measures of implementing Article 9 of the International Treaty submitted by AfricaRice, Bioversity International, CIAT, CIMMYT, ICARDA, ICRISAT and IRRI on 23 July 2019.